Medieval women in their communities - Watt, Diane, 1965- (University of Toronto Press, 1997)
"The lives of women in religious communities in late medieval Europe are the main focus of this volume which brings together a body of original research by historians and literary scholars and discusses a variety of such communities in France, Germany and Wales. The perspective is also broadened to include the lives of women in relation to the local community in places as far apart as East Anglian and southern Italy."--Jacket.